2020
DOI: 10.2147/ijn.s247114
|View full text |Cite
|
Sign up to set email alerts
|

<p>Nanotechnology-Based Cisplatin Intracellular Delivery to Enhance Chemo-Sensitivity of Ovarian Cancer</p>

Abstract: Background: Platinum resistance is a major challenge in the management of ovarian cancer. Even low levels of acquired resistance at the cellular level lead to impaired response to cisplatin. In ovarian cancer intraperitoneal therapy, nanoparticle formulation can improve the cisplatin's pharmacokinetics and safety profile. Purpose: This work aimed to investigate the chemo-sensitivity of ovarian cancer SKOV3 cells upon short-term (72h) single treatment of cisplatin and cisplatin-loaded biodegradable nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…12 J). Recently, cisplatin and cisplatin-loaded NP were recently evaluated at 10.00 and 30.00 µM concentrations 49 . In their study, the morphology of cells treated with free cisplatin differed significantly from that of cells treated with cisplatin-loaded nanoparticles, with irregular forms, shrinkage, rounding, and detachment in the cisplatin-treated samples.…”
Section: Resultsmentioning
confidence: 99%
“…12 J). Recently, cisplatin and cisplatin-loaded NP were recently evaluated at 10.00 and 30.00 µM concentrations 49 . In their study, the morphology of cells treated with free cisplatin differed significantly from that of cells treated with cisplatin-loaded nanoparticles, with irregular forms, shrinkage, rounding, and detachment in the cisplatin-treated samples.…”
Section: Resultsmentioning
confidence: 99%
“…During his research, he found that microscopic images of dividing cells resembled the pattern of iron shavings exposed to a magnetic field and implied that an electrical area might also influence cell division. However, the studies reports had declared that platinum has no biological records, so they used platinum electrodes in a solution containing the standard laboratory bacteria "E. coil" in their experiment [25]. Further, the bacterial cells were immobile and did not divide as soon as the current was turned on, yet they continued to grow to 300 times their average length and began to separate again after the power was turned off.…”
Section: Cisplatinmentioning
confidence: 99%
“…Nanoliposomal formulations of cisplatin (termed lipoplatin) are part of standard oncological care, having passed the clinical trial phase, showing high dose accumulation in tumor sites, where they are thought to act as both chemotherapeutic and antiangiogenic agents [ 74 ]. Other strategies include gold nanocarriers and physical force methods such as magnetism, ultrasound, and heat [ 75 , 76 ]. Several studies were conducted for the development of cisplatin-loaded chitosan nanoparticles with successful results in terms of in vitro cytotoxicity and kinetics [ 77 , 78 , 79 ].…”
Section: Myocardial Toxicity Induced By Oncological Drugs and Prevent...mentioning
confidence: 99%